Artificial Intelligence: Governments Large and Small Take on the Issues - P.H. Longstaff (International Telecommunications Society (ITS), 2019)
This paper sets out the current discussions around the world on the issue of Artificial Intelligence. Several themes seem to be apparent and are set out here. It is important to know that this is a snapshot of these discussions and the author apologizes in advance that research has only been done in English. The top few topics being discussed are then briefly discussed as areas where all governments may put some of their efforts.
Keywords: 330